2009
DOI: 10.5539/ijbm.v4n4p3
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effect of Empowerment in the Relationship between Transformational Leadership and Service Quality

Abstract: Transformational leadership has two salient characteristics: intellectual stimulation and individualized consideration. Recent studies in this area reveal that the effect of such leadership characteristics on job performance is indirectly affected by empowerment. The nature of this relationship is interesting, but little is known about the mediating effect of empowerment in leadership management models. Therefore, this study was conducted to measure the effect of transformational leadership characteristics and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 39 publications
1
25
0
2
Order By: Relevance
“…Transformational leadership style focuses on the development of followers and their needs. Managers exercising transformational leadership style focus on the development of value system of employees, their motivational level and moralities with the development of their skills (Ismail et al, 2009) transformational leadership acts as a bridge between leaders and followers to develop clear understanding of follower's interests, values and motivational level it basically helps follower's achieve their goals working in the organizational setting; it encourages follower's to be expressive and adaptive to new and improved practices and changes in the environment. (Bycio et al, 1978) Burn's (1978) transformational theory and Bass's (1985) transformational leadership theory explained these characteristics of leadership style.…”
Section: Transformational Leadership Stylementioning
confidence: 99%
“…Transformational leadership style focuses on the development of followers and their needs. Managers exercising transformational leadership style focus on the development of value system of employees, their motivational level and moralities with the development of their skills (Ismail et al, 2009) transformational leadership acts as a bridge between leaders and followers to develop clear understanding of follower's interests, values and motivational level it basically helps follower's achieve their goals working in the organizational setting; it encourages follower's to be expressive and adaptive to new and improved practices and changes in the environment. (Bycio et al, 1978) Burn's (1978) transformational theory and Bass's (1985) transformational leadership theory explained these characteristics of leadership style.…”
Section: Transformational Leadership Stylementioning
confidence: 99%
“…Ismail et al [27] see an effective leader as one who is able to convince employees to toe a particular line of action especially when it has to do with strategies for meeting organizational targets. Judge et al [28] support this position and maintains that the quality of leadership, to a large extent, should determine employee performance and by extension corporate readiness to achieve set targets.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…The study (Ismail et al, 2009) indicated that managers of health institutions have a significant impact on quality of service.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of studies have been done related to the relationship between leadership and service quality (Azbari & Chaijani, 2015), (Jabnoun & Juma, 2005) (Ismail et al, 2009) However, these studies did not take into consecration the security conditions and did not address this issue within a sample in light of the difficult security situation and the face of terrorism in some places like Iraq, The study of (Ehsani et al, 2012) indicates that leadership has a direct significant impact on job satisfaction, and this relationship is positively reflected on improving the quality of service.…”
Section: Introductionmentioning
confidence: 99%